Allelopathic potential of the plant extract from the stem of Cuscuta campestris Yunck. - Tojić, Teodora; Gajić Umiljendić, Jelena; }or]evi', Tijana; Sarić-Krsmanović, Marija M (Acta herbologica, 2024)
Allelopathic processes involve interactions between living organisms that take place via secondary metabolites (allelochemicals). Cuscuta species are known for their large production of chemical compounds characterized by various biological activities. The aim of this study was to test the allelopathic effects of the plant extracts isolated from stem of Cuscuta campestris on the germination and early seedling growth of two weed species (Amaranthus retroflexus and Portulaca oleracea). Additionally, the goals were to also conduct an analysis of the plant extracts and determine its antioxidant properties.The chemical analysis showed that obtained plant extract is a rich source of phenolic compounds. HPLC analysis separated by content the following compounds: quercetin (5.62 mg/g), catechin (3.71 mg/g), diadzin (2.85 mg/g), luteolin (1.82 mg/g), and rutin (1.16 mg/g). In addition, higher concentrations (0.75% and 1%) of the plant extract of this parasitic flower had an inhibitory effect on the germination and early growth of A. retroflexus and P. oleracea seeds. A. retroflexus proved to be a more sensitive test plant compared to P. oleraceae, which is confirmed by the inhibition percentages of seed germination of 88% (A. retroflexus) and 8% (P. oleraceae), i.e. the inhibition of seedling growth was 77% (A. retroflexus), or 70% (P. oleraceae). Future research must include plant biossay trials as well as field microtrials to determine allelopathic effects on weed species.